Purify and purge. The Civil War in Cinco Villas from a feminist perspective - Sánchez, Cristina (Filanderas, 2019)
In the last decades the feminist perspective has contributed to change traditional historiography, improving Spanish Civil War studies by the incorporation of women into the common narrative.Due to its specified situation and war context, Aragón is one of the best territories to study and better understand the Spanish conflict. Because of its strong republicanism and socialisms, las Cinco Villas was severely subdued by the Francoism and its violence. The region stayed always in rearguard, because it fell into Franco’s hands from the beginning. Women were object of all that repression, including some particular violence that men did not suffered. There were head shaves, humiliating exhibitions, rapes, detentions and murders in Ejea de los Caballeros, Sos del Rey Católico, Tauste, Farasdués or Uncastillo.
Keywords: Spanish Civil War; Francoism; Political violence; Sexed violence; Cinco Villas